INDUSTRIAL SAFETY IMPLEMENTATION ANALYSIS IN MANUFACTURING COMPANIES IN ARANDAS - Celina Beltrán-Hernández; José Salvador Barragán-Hernández; Luis Alfredo Castañeda-Andrade (Ra Ximhai, 2018)
This study was done to perform an analysis to the manufacturing productive sector companies in Arandas using a quantitative approach to confront the deficiencies found according to the STPS norms which apply to the different sectors. Companies grow constantly and leave aside the security aspect for later, losing their essence; which is why it is important to identify the deficit in which they are; being this a growth opportunity; since this is one of the main pillars of the organization, solving it from a professional, ethical and efficient approach through the implementation of different norms which must be taken into consideration according to the specific area where they mainly operate.